Teknik Pengolahan Hasil Asesmen Pendidikan Agama Islam (Penentuan Standar Asesmen, Teknik Pengolahan dengan Menggunakan Pendekatan Penilaian Acuan Patokan (PAP), dan Acuan Norma (PAN) di SMK Muhammadiyah Mlati Yogyakarta) - Feri Riski Dinata (Jurnal Al-Hikmah, 2020)
In this research will discuss some topics of discussion related to assessment processing techniques and the determination of assessment standards. This research took background SMK Muhammadiyah Mlati Yogyakarta, while in collecting data writer earn from bpk. Muh Sholikul Hadi as teacher of PAI. The form of assessment processing there are two kinds, namely, processing techniques using benchmark reference approach and norm reference. To conduct an assessment of the student's learning outcomes, a teacher determines the value of the tester should be processed from the raw score obtained by the benchmark reference approach or the norm reference. In general, the steps undertaken by the tester in conducting the assessment of this are: First: scoring in advance of the results of learning test learners. Second: turn the raw score into a standard score. Third: convert standard score into value. The final activity of processing the assessment results in the form of converting the score to the value, either in the form of letters or numbers. The results of the assessment of the results of this assessment will be used in the interpretation of assessment results. To facilitate the interpretation of the results of the assessment, the final results of processing the assessment results can be administrated properly.